2012
DOI: 10.1002/anie.201205051
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Functionalization of Unactivated C(sp3)H Bonds by Hydride Transfer Facilitated by Alkynylspirocyclopropanes

Abstract: A Golden Gate: Alkynylspirocyclopropanes served as a template for the development of gold‐catalyzed hydride transfer from unactivated C(sp3)H bonds to electronically neutral alkynes. A variety of interesting carbocyclic structures can be accessed selectively with the appropriate choice of the reaction conditions. Mechanistic studies support a sequential gold‐catalyzed cleavage of CH and CC bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…In 2012, Ballesteros et al discovered an unprecedented goldcatalyzed 1,5-hydride shift process from an unreactive methylene C-H bonds to the alkyne, leading to the subsequent selective cyclization (Scheme 19). 33 The restricted geometry in 81 may facilitate the 1,5-hydride shift to the gold-activated alkyne. From the screening of reaction conditions, it was found that the products could be controlled under microwave irradiation by simply changing the gold-complex or reaction temperature.…”
Section: Gold-catalyzed Redox-neutral C(sp 3 )-H Bond Functionalizationmentioning
confidence: 99%
“…In 2012, Ballesteros et al discovered an unprecedented goldcatalyzed 1,5-hydride shift process from an unreactive methylene C-H bonds to the alkyne, leading to the subsequent selective cyclization (Scheme 19). 33 The restricted geometry in 81 may facilitate the 1,5-hydride shift to the gold-activated alkyne. From the screening of reaction conditions, it was found that the products could be controlled under microwave irradiation by simply changing the gold-complex or reaction temperature.…”
Section: Gold-catalyzed Redox-neutral C(sp 3 )-H Bond Functionalizationmentioning
confidence: 99%
“…In 2012, Barluenga and co‐workers elegantly demonstrated an intriguing manifold reactivity of alkynylcyclopropanes 221 that bear a spirane core (Scheme ) 58. Remarkably, a comparatively inactive non‐benzylic secondary CH bond could work as hydride donor.…”
Section: Non‐benzylic C(sp3)h Bondsmentioning
confidence: 99%
“…When the different functional groups were introduced the cyclopentadienyl group of the compound, the effects were mainly electron effect and steric hindrance. 33 The overwhelming steric hindrance will prevent olefin insertion reaction, resulting in inactivation of catalyst. The bonding orbital of different metallocene compounds is calculated ( Fig.…”
Section: Resultsmentioning
confidence: 99%